The Effect of Multilayer Nanoemulsion on the In Vitro Digestion and Antioxidant Activity of β-Carotene - Mei Zi Sun; Do-Yeong Kim; Youjin Baek; Hyeon Gyu Lee (MDPI AG, 2024)
The objectives of this study were to design multilayer oil-in-water nanoemulsions using a layer-by-layer technique to enhance the stability of β-carotene and evaluate its effect on in vitro release and antioxidant activity. To prepare β-carotene-loaded multilayer nanoemulsions (NEs), a primary NE (PRI-NE) using Tween 20 was coated with chitosan (CS) for the secondary NE (SEC-CS), and with dextran sulfate (DS) and sodium alginate (SA) for the two types of tertiary NEs (TER-DS, TER-SA). The multilayer NEs ranged in particle size from 92 to 110 nm and exhibited high entrapment efficiency (92-99%). After incubation in a simulated gastrointestinal tract model, the release rate of free fatty acids decreased slightly after coating with CS, DS, and SA. The bioaccessibility of β-carotene was 7.02% for the PRI-NE, 7.96% for the SEC-CS, 10.88% for the TER-DS, and 10.25% for the TER-SA. The 2,2-diphenyl-1-picrylhydrazyl radical scavenging abilities increased by 1.2 times for the multilayer NEs compared to the PRI-NE. In addition, the cellular antioxidant abilities improved by 1.8 times for the TER-DS (87.24%) compared to the PRI-NE (48.36%). Therefore, multilayer nanoemulsions are potentially valuable techniques to improve the stability, in vitro digestion, and antioxidant activity of β-carotene.